Peran Peran Konseling Individual Dengan Metode Mindfulness Dalam memgatasi Kecemasan Pada Remaja Di LPKA Kelas I Palembang - Poppy Ulandari; Abdur Razzaq; Lena Marianti (Scidacplus, 2023)
Anxiety is a normal thing that can happen to every individual, but anxiety can be said to be deviant if the individual is unable to reduce the anxiety in situations where most people are able to handle it without any significant difficulties. This research is entitled